Geology for ground engineering projects - Fletcher, Chris J. N. (CRC Press/Taylor & Francis, 2016)
Geology for Ground Engineering Projects is well illustrated with color diagrams and photographs. Readers are directed to satellite images of selected areas to explore for themselves many of the geological features described in this book.